Retrospective analysis of non-laboratory-based adverse drug reactions induced by intravenous radiocontrast agents in a Joint Commission International-accredited academic medical center hospital in China - Chen QL; Zhao XY; Wang XM; Lv N; Zhu LL; Xu HM; Zhou Q (Dove Medical Press, 2017)
Qin-lan Chen,1 Xiao-ying Zhao,2 Xiao-mi Wang,1 Na Lv,2 Ling-ling Zhu,3 Hui-min Xu,4 Quan Zhou4 1Radiology Nursing Unit, Division of Nursing, 2Department of Quality Management, 3Geriatric VIP Care Ward, Division of Nursing, 4Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of China Abstract: The authors retrospectively analyzed the pattern and characteristics of non-laboratory-based adverse drug reactions (ADRs) induced by intravenous radiocontrast agents in a large-scale hospital in China during 2014–2015. There were 314 ADR cases among 118,208 patients receiving enhanced CT or MRI examinations. The frequency of moderate/severe ADRs defined by Chinese Society of Radiology (ie, severe vomiting, systematic urticaria, facial swelling, dyspnea, vasovagal reaction, laryngeal edema, seizure, trembling, convulsions, unconsciousness, shock, death, and other unexpected adverse reactions) was rare (0.0431%), whereas the mild ADRs were uncommon (0.2225%) and accounted for 83.76% of ADRs. Frequency of ADRs induced by iodinated contrast agents was related with examination site, sex, and type of patient settings (P<0.01) and was higher compared with gadolinium contrast agents (0.3676% vs 0.0504%, P<0.01). From 2014 to 2015, frequencies of total and moderate/severe ADRs induced by iodinated contrast agents decreased significantly (0.4410% vs 0.2947%, P<0.01; 0.0960% vs 0.0282%, P<0.01, respectively). Frequency of ADRs differed among different iodinated contrast and gadolinium contrast (P<0.05) agents. Iopromide’s ADR frequency in 2014 was significantly higher compared with iopamidol, ioversol, or iohexol (P<0.01). Frequency of moderate/severe ADRs induced by iodixanol was 4.1–5.4 times that of iohexol, iopromide, or iopamidol. Rash was the predominant ADR subtype (84.39%) and occurred more frequently with iodixanol compared with iohexol, iopamidol, or ioversol (P<0.01). Overall, 21.97% of ADR cases had allergy history or atopy traits, and these cases experienced ADRs earlier than the negative ones (17.19 min vs 85.34 min, P<0.01). The mean time to onset of ADRs was increased in patients receiving iodixanol compared with other iodinated contrast agents (323.77 min vs 42.36 min, P<0.01). Overall, 37.26% of ADRs occurred within 5 min and 84.08% of ADRs occurred within 30 min. Efficient quality improvement in decreasing ADRs induced by radiocontrast agents has been achieved by multidisciplinary collaboration. Keywords: allergy, atopy, contrast media, drug monitoring, gadolinium contrast, iodinated contrast, quality improvements